We are growing! - Keller, Laurie; Willems, Mo (New York : Hyperion Books for Children, 2016)
Walt is not the tallest or the curliest or the pointiest or even the crunchiest. A confounded blade of grass searches for his 'est' in this story about growing up.
School Library Journal, August 2016.
Booklist starred, July 2016.
Kirkus Review, July 2016.
Publishers Weekly Annex, September 2016.
1.1
K-3
Keywords: Growth -- Juvenile fiction; Grasses -- Juvenile fiction; Growth -- Fiction; Growth -- Fiction; Humorous stories; Humorous fiction; Readers (Elementary)